The Role of Angiotensin-(1-7)/Mas Axis and Angiotensin Type 2 Receptors in the Central Nervous System in Cardiovascular Disease and Therapeutics: A Riddle to be Solved - Katsi, Vasiliki; Maragkoudakis, Spyridon; Marketou, Maria; Tsioufis, Costas; Parthenakis, Fragkiskos; Tousoulis, Dimitrios (Current Vascular Pharmacology, 2019)
In recent years, the Angiotensin-(1-7)/Mas receptor [Ang-(1-7)/Mas] sub-branch of the Renin-Angiotensin System (RAS) in the brain, and Angiotensin Type 2 Receptors (AT2R), have attracted scientific interest, as there is evidence that they constitute an essential pathway in cardiovascular regulation, in health and in disease. By acting centrally, the Ang-(1-7)/Mas axis - that has been termed ‘the axis of good’- can exert blood pressure-lowering effects, while also favourably altering baroreflex sensitivity and noradrenergic neurotransmission. Thus, research has focused on the possible neuro- and cardioprotective effects of this pathway in the setting of cardiovascular disease, ultimately aiming to evaluate the potential for development of novel therapeutic strategies based on its modulation. We summarize the available evidence from experimental studies in this context, aiming to assess current limits of scientific knowledge relevant to this newly-described ‘player’ in haemodynamic regulation, that may become a potential therapeutic target.
Keywords: angiotensin converting enzyme 2